SPATHOLOBUS SUBERECTUS STEM EXTRACT IMPROVES THE PROTECTIVE EFFECT OF HEPARIN ON CERULEIN–INDUCED PANCREATITIS - Shao, Zhengyi (African Journal of Traditional, Complementary and Alternative Medicines, 2017)
of pancreatitis alone and in combination with heparin.Material and methods: Pancreatitis was induced pancreatitis by cerulean (50μg/kg, i.p.) five times at an interval of 1 hwithout any pretreatment of drug. Rats were treated with SS (100 and 200 mg/kg, p. o.) and heparin (150 U/kg, i.p.)alone and in combination for the duration of a week. Later pancreatic weight and blood flow was estimated anddifferent biochemical parameters like concentration of D-dimer and Interleukin 1β (IL-1β) and activity of amylase andlipase were determined in blood of pancreatitis rats. Moreover effect of drug treatment on DNA synthesis andhistopathology was also estimated on cerulean induced pancreatitis rats.Result: Results of this study suggest that treatment with SS alone and in combination with heparin significantlyincrease in prothrombin time and pancreatic blood flow than negative control group. There was significant decrease inconcentration of IL-1β and D-dimer and activity of amylase and lipase in SS and heparin treated group than negativecontrol group. Pancreatic DNA synthesis was also found to be reduced in SS and heparin alone and in combinationtreated group. Histopathology study also reveals that treatment with SS and heparin alone and in combination reducesedema, hemorrhages, leukocyte infiltration in the TS of pancreatic tissues. Conclusion: Present study concludes thattreatment with SS alone effectively manages the pancreatitis by ceasing the inflammatory pathway and potentiates theeffect of heparin in the management of pancreatitis.